Using Canvas LMS learning outcomes assessment and program improvement - Frederick Burrack (Academic Chairpersons Conference Proceedings, 2023)
This session will provide a step-by-step process of creating program outcomes in Canvas. These outcomes are aligned with assessment tasks through the scoring devices used in courses, internships, or other course-based means through which students demonstrate outcomes proficiencies.
Keywords: Assessment; Learning; Effectiveness; Improvement